Positive electrode and rechargeable lithium battery including same

By employing a double-layer active material layer design in the positive electrode of a rechargeable lithium battery, and utilizing a combination of olivine, layered compound particles, and conductive materials, the problem of insufficient adhesion of the positive electrode is solved, thereby improving the battery's capacity and lifespan.

CN120878729APending Publication Date: 2025-10-31SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510545301.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-29
Filing Date
2025-04-28
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

The positive electrode of existing rechargeable lithium batteries has insufficient adhesion during the manufacturing process, resulting in poor performance of the electrode plate and affecting the battery's capacity and lifespan.

Method used

The positive electrode adopts a double-layer structure. The first positive electrode active material layer consists of olivine-structured compound particles and layered compound particles, combined with conductive materials and binders. The second active material layer also uses olivine-structured compound particles, conductive materials and binders. The adhesion is improved by adjusting the weight ratio between the two.

Benefits of technology

It improves the adhesion of the positive electrode, enhances the fabrication efficiency of the electrode plate, and improves the capacity and lifespan characteristics of the rechargeable lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120878729A_ABST
    Figure CN120878729A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode and a rechargeable lithium battery including the same. A positive electrode for a rechargeable lithium battery includes a positive electrode current collector, a first positive electrode active material layer on the positive electrode current collector, and a second positive electrode active material layer on the first positive electrode active material layer. The first positive electrode active material layer includes first particles of a compound structured by olivine represented by Formula 1, second particles of a layered compound represented by Formula 2, a first conductive material, and a first binder. The second positive electrode active material layer includes third particles of a compound structured by olivine represented by Formula 3, a second conductive material, and a second binder. The first particle is in the form of a single particle and the third particle is in the form of a secondary particle. A formula 1 is Lia1Fex1B1y1PO4-c < 1 >, a formula 2 is Lia2Nix2Coy2B2z2O2-c < 2 >, and a formula 3 is Lia3Fex3B3y3PO4-c < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This patent application claims priority to Korean Patent Application No. 10-2024-0057143, filed on April 29, 2024, the entire contents of which are incorporated herein by reference. Background Technology

[0003] This disclosure relates to a positive electrode and a rechargeable lithium battery including a positive electrode. More specifically, aspects of this disclosure relate to a positive electrode including an olivine-based lithium compound (an olivine-structured compound) and a rechargeable lithium battery including a positive electrode.

[0004] The rapid proliferation of battery-powered devices, such as mobile phones, laptops, and electric vehicles, has driven a dramatic increase in demand for rechargeable lithium-ion batteries with high energy density and capacity. Accordingly, extensive research efforts have been directed towards improving the performance of rechargeable lithium-ion batteries.

[0005] A rechargeable lithium-ion battery includes a positive electrode and a negative electrode (each containing active materials that allow lithium ions to be inserted into and extracted from the electrodes) and an electrolyte. The battery generates electrical energy through a redox reaction that occurs when lithium ions are inserted into or extracted from the positive and negative electrodes. Summary of the Invention

[0006] This disclosure provides a positive electrode that allows for easy fabrication of an electrode plate by increasing the adhesion between the positive electrode current collector and the positive electrode active material.

[0007] This disclosure also provides a positive electrode with improved capacity and lifetime characteristics.

[0008] Embodiments of this disclosure provide a positive electrode for a rechargeable lithium battery, comprising: a positive electrode current collector, a first positive electrode active material layer on the positive electrode current collector, and a second positive electrode active material layer on the first positive electrode active material layer. The first positive electrode active material layer comprises first particles of a olivine-structured compound represented by Formula 1, second particles of a layered compound represented by Formula 2, a first conductive material, and a first binder. The second positive electrode active material layer comprises third particles of a olivine-structured compound represented by Formula 3, a second conductive material, and a second binder. The first particles are in the form of single particles, and the third particles are in the form of secondary particles. The first binder and the first conductive material constitute a first functional additive, and the second binder and the second conductive material constitute a second functional additive. The weight ratio of the second functional additive in the second positive electrode active material layer to the weight ratio of the first functional additive in the first positive electrode active material layer is approximately 1.0 to approximately 2.03, wherein Formula 1 is:

[0009] Li

[0014] , Fe x1 B1 y1 PO 4-c1

[0010] where 0.8 < a1 ≤ 1.2, 0.95 ≤ x1 ≤ 0.999, 0.001 ≤ y1 ≤ 0.05, x1 + y1 = 1, and 0 ≤ c1 ≤ 0.05, and B1 is at least one of Ti and a transition metal with an oxidation number of 4, and Formula 2 is:

[0011] Li a2 Ni x2 Co y2 B2 z2 O 2-c2

[0012] where 0.8 < a2 ≤ 1.2, 0.9 ≤ x2 ≤ 1.05, 0.03 ≤ y2 ≤ 0.10, 0.01 ≤ z2 ≤ 0.05, and 0 ≤ c2 ≤ 0.05, and B2 is at least one of Al and Mn, and Formula 3 is:

[0013] Li a3 Fe x3 B3 y3 PO[[ID=​​​​​​​​​​​​​​​​​​where 0.8 < a1 ≤ 1.2, 0.95 ≤ x1 ≤ 0.999, 0.001 ≤ y1 ≤ 0.05, x1 + y1 = 1, and 0 ≤ c1 ≤ 0.05, and B1 is at least one of Ti and a transition metal with an oxidation number of 4, and Formula 2 is:

[0018] Li a2 Ni x2 Co y2 B2 z2 O 2-c2

[0019] where 0.8 < a2 ≤ 1.2, 0.9 ≤ x2 ≤ 1.05, 0.03 ≤ y2 ≤ 0.10, 0.01 ≤ z2 ≤ 0.05, and 0 ≤ c2 ≤ 0.05, and B2 is at least one of Al and Mn, and Formula 3 is:

[0020] Li a3 Fe x3 B3 y3 PO 4-c3

[0021] where 0.8 < a3 ≤ 1.2, 0.95 ≤ x3 ≤ 0.999, 0.001 ≤ y3 ≤ 0.05, x3 + y3 = 1, and 0 ≤ c3 ≤ 0.05, and B3 is at least one of Ti and a transition metal with an oxidation number of 4.

[0022] In an embodiment of the present disclosure, the rechargeable lithium battery includes the above positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are included to provide a further understanding of the present disclosure, and the accompanying drawings are incorporated into and constitute a part of this specification. The drawings illustrate embodiments of the present disclosure and are used together with this description to explain the principles of the present disclosure. In the drawings:

[0024] Figure 1 is a simplified conceptual diagram showing an embodiment of a rechargeable lithium battery according to the present disclosure;

[0025] Figures 2-5 is a schematic diagram showing a rechargeable lithium battery according to an embodiment, where Figure 2 shows a cylindrical battery, Figure 3 shows a prismatic battery, and Figure 4 and Figure 5 shows a pouch-type battery;

[0026] Figure 6 is a cross-sectional view showing a positive electrode for a rechargeable lithium battery according to an embodiment of the present disclosure;

[0027] Figure 7An enlarged view showing the first positive electrode active material layer according to an embodiment of the present disclosure;

[0028] Figure 8 An enlarged view showing the second positive electrode active material layer according to an embodiment of the present disclosure;

[0029] Figure 9 To show a SEM image of the first particle of Preparation Example 1 according to the present disclosure;

[0030] Figure 10 To show a SEM image of the second particle (having a single particle form) of Preparation Example 2 according to the present disclosure;

[0031] Figure 11 To illustrate a SEM image of a second particle (having a secondary particle form) according to an embodiment of this disclosure; and

[0032] Figure 12 To show a SEM image of the third particle of Preparation Example 3 according to the present disclosure. Detailed Implementation

[0033] To fully understand the layout and effects of this disclosure, some embodiments of the disclosure will be described with reference to the accompanying drawings. However, it should be noted that this disclosure is not limited to the exemplary embodiments described below and can be implemented in various forms. Rather, exemplary embodiments are provided only to disclose this disclosure and to enable those skilled in the art to fully understand its scope.

[0034] In this description, it will be understood that when an element is referred to as being on another element, the element may be directly on the other element, or an intervening element may exist between the two. In the accompanying drawings, the dimensions (e.g., thickness) of some components are enlarged for the purpose of effectively explaining the technical content. Throughout the specification, the same reference numerals refer to the same elements.

[0035] The embodiments described herein are explained with reference to cross-sectional and / or plan views, which serve as ideal example views of this disclosure. In the figures, the thickness of the membranes and regions is enlarged for efficient description of the technical content. Therefore, the regions presented as examples in the figures have conventional properties, and the shapes of the exemplified regions are used to illustrate the specific shapes of the device regions. Therefore, this should not be construed as limiting the scope of this disclosure. Although terms (such as first, second, and third) are used to describe various components in the various embodiments herein, these components should not be limited to these terms. These terms are merely used to distinguish one component from another. The embodiments described and exemplified herein include their complementary embodiments.

[0036] Unless otherwise specified in this description, singular expressions may include plural expressions. Additionally, unless otherwise specified, the phrase "A or B" may indicate "A but not B", "B but not A", and "A and B". The terms "comprises / includes" and / or "comprising / including" as used in this description do not exclude the presence or addition of one or more other components.

[0037] As used herein, the term "combination thereof" may refer to mixtures, stacks, complexes, copolymers, alloys, blends, or reaction products.

[0038] Unless otherwise specifically defined in this description, particle size may refer to the average particle size (average diameter). Additionally, particle size indicates the average diameter (D) of the cumulative volume over 50 vol% of the particle size distribution. 50 Average diameter (D) 50 The particle size distribution (D) can be measured using methods known to those skilled in the art, such as by a particle size analyzer, transmission electron microscopy (TEM) images, or scanning electron microscopy (SEM) images. Alternatively, a dynamic light scattering measurement device can be used for data analysis, counting the number of particles for each particle size range, and then calculating the average diameter (D) from this. 50 The laser scattering method can also be used to measure the average diameter (D). 50 In the laser scattering method, target particles are dispersed in a dispersion medium and introduced into a laser scattering particle size measuring device (e.g., the MT3000, commercially available from Microtrac, Inc.) and irradiated with ultrasound at a power of 60 W and a frequency of 28 kHz. The average diameter (D) is then calculated in the measuring device based on approximately 50% diameter distribution. 50 ).

[0039] Figure 1 This is a cross-sectional view of an embodiment of a rechargeable lithium battery according to the present disclosure. (Refer to...) Figure 1 A rechargeable lithium battery may include a positive electrode 10, a negative electrode 20, a separator 30, and an electrolyte ELL.

[0040] The positive electrode 10 and the negative electrode 20 may be spaced apart from each other by a diaphragm 30. The diaphragm 30 may be disposed between the positive electrode 10 and the negative electrode 20. The positive electrode 10, the negative electrode 20 and the diaphragm 30 may be in contact with the electrolyte ELL. In particular, the positive electrode 10, the negative electrode 20 and the diaphragm 30 may be immersed in the electrolyte ELL.

[0041] The electrolyte ELL can be used as a medium for transporting lithium ions between the positive electrode 10 and the negative electrode 20. In the electrolyte ELL, lithium ions can move towards the positive electrode 10 or the negative electrode 20 through the separator 30.

[0042] positive electrode

[0043] The positive electrode 10 for a rechargeable lithium battery may include a positive electrode current collector COL1 and a positive electrode active material layer AML1 formed on the positive electrode current collector COL1. The positive electrode active material layer AML1 may include a positive electrode active material and may further include a binder and / or a conductive material.

[0044] The positive electrode 10 may further include components that can be used as a sacrificial positive electrode.

[0045] Al foil can be used in the positive electrode current collector COL1, but this disclosure is not limited thereto.

[0046] The following will refer to Figure 6 The positive electrode 10 according to embodiments of the present disclosure is described in detail.

[0047] negative electrode

[0048] The negative electrode 20 for a rechargeable lithium battery may include a negative electrode current collector COL2 and a negative electrode active material layer AML2 on the negative electrode current collector COL2. The negative electrode active material layer AML2 may include a negative electrode active material, and the negative electrode active material layer may further include a binder and / or a conductive material (e.g., an electrically conductive material).

[0049] The negative electrode active material layer AML2 may include about 90 wt% to about 99.5 wt% of negative electrode active material, about 0.5 wt% to about 5 wt% of binder and about 0 wt% to about 5 wt% of conductive material.

[0050] The binder can be used to adhere the negative electrode active material particles to each other, and also to adhere the negative electrode active material to the negative electrode current collector COL2. The binder may include non-aqueous binders, aqueous binders, dry binders, or combinations thereof.

[0051] Non-aqueous adhesives may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.

[0052] Waterborne adhesives may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.

[0053] When an aqueous binder is used as a binder in the negative electrode active material layer AML2, it may further include a cellulose compound capable of imparting viscosity. The cellulose compound may include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and their alkali metal salts. The alkali metal may include Na, K, or Li.

[0054] Dry adhesives can be fibrous polymer materials. For example, dry adhesives can be polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0055] Conductive materials can be used to impart conductivity (e.g., electrical conductivity) to electrodes. Any material that does not cause chemical changes (e.g., does not cause undesirable chemical changes in rechargeable lithium batteries) and conducts electrons can be used in batteries. Non-limiting examples of conductive materials include: carbon-based materials (such as natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes); metallic materials, including copper, nickel, aluminum, silver, etc., in the form of metal powders or metal fibers; conductive polymers (such as polyphenylene derivatives); or mixtures thereof.

[0056] The negative electrode current collector COL2 may include copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.

[0057] Negative electrode active material

[0058] The negative electrode active material may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials that can be doped / dedoped with lithium, or transition metal oxides.

[0059] Materials that can reversibly insert / deintercalate lithium ions can include carbon-based negative electrode active materials (such as crystalline carbon, amorphous carbon, or combinations thereof). Crystalline carbon can be graphite (such as amorphous, flake, sheet, spherical, or fibrous natural or artificial graphite). Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbonization products, calcined coke, etc.

[0060] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0061] The material capable of doping / dedoping lithium can be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material can include silicon, silicon-carbon composite, SiO x (0 < x ≤ 2), Si-Q alloy, or a combination. In the Si-Q alloy, Q is selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof. The Sn-based negative electrode active material can include Sn, SnO x (0 < x ≤ 2) (for example, SnO2), Sn-based alloy, or a combination thereof.

[0062] The silicon-carbon composite can be a composite of silicon and amorphous carbon. According to an embodiment, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite can include secondary particles (cores) in which primary silicon particles are coalesced and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be between the primary silicon particles, and, for example, the primary silicon particles can be coated with amorphous carbon. The secondary particles are dispersed in the amorphous carbon matrix.

[0063] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include a core containing crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core.

[0064] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used in combination with a carbon-based negative electrode active material.

[0065] diaphragm

[0066] Depending on the type of rechargeable lithium battery, the separator 30 can be present between the positive electrode 10 and the negative electrode 20. The separator 30 can include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more of them (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0067] The separator 30 can include a porous substrate and a coating on one or both surfaces of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof.

[0068] The porous substrate may be a polymer film formed from polymers or copolymers or mixtures of two or more of the following polymers: polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and polytetrafluoroethylene (e.g., ).

[0069] Organic materials may include polymers such as polyvinylidene fluoride or (meth)acrylic acid polymers.

[0070] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. However, this disclosure is not limited to these examples.

[0071] Organic and inorganic materials can be mixed in a coating, or coatings containing organic materials and coatings containing inorganic materials can be stacked.

[0072] electrolyte

[0073] Electrolytes (ELLs) used in rechargeable lithium batteries may include non-aqueous organic solvents and lithium salts.

[0074] Non-aqueous organic solvents can be used as media for transporting ions that participate in the electrochemical reactions of a battery.

[0075] Non-aqueous organic solvents may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or combinations thereof.

[0076] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc.

[0077] Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.

[0078] Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, ethylene glycol dimethyl ether, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Additionally, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitrile solvents (such as R-CN (where R is a C2-C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, or ether bonds, etc.); amides (such as dimethylformamide); dioxolane (such as 1,3-dioxolane, 1,4-dioxolane, etc.); sulfolane, etc.

[0079] Non-aqueous organic solvents can be used alone or in combination of two or more.

[0080] In addition, when using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.

[0081] Lithium salts dissolved in non-aqueous organic solvents supply lithium ions in batteries, ensuring basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide), LiFSI, LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluoro(oxalate)borate (LiDFOB), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0082] Rechargeable lithium batteries

[0083] Rechargeable lithium batteries can be classified according to their shape as cylindrical, prismatic, pouch, or coin-shaped batteries, etc. Figures 2-5 A schematic diagram illustrating a rechargeable lithium battery according to an embodiment. Figure 2 A cylindrical battery is shown. Figure 3 A prismatic battery is shown, and Figure 4 and Figure 5 A pouch-type battery is shown. (Reference) Figures 2-5, the rechargeable lithium battery 100 may include an electrode assembly 40 and a housing 50 that includes the electrode assembly 40. The electrode assembly 40 includes a separator 30 between a positive electrode 10 and a negative electrode 20. The positive electrode 10, negative electrode 20, and separator 30 may be impregnated with an electrolyte (not shown). The rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50, as Figure 2 shown. In Figure 3 , the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As Figure 4 and Figure 5 shown, the rechargeable lithium battery 100 may include electrode tabs 70, which may be, for example, a positive electrode tab 71 and a negative electrode tab 72 that function to guide the current generated in the electrode assembly 40 to the outside of the battery.

[0084] As a non-limiting example, the rechargeable lithium battery according to an embodiment may be used in an automobile, a mobile phone, and / or various types of electronic devices.

[0085] Hereinafter, the first particle PTC1, the second particle PTC2, the third particle PTC3, the first positive electrode active material layer ATL1, the second positive electrode active material layer ATL2, and the positive electrode having a bilayer structure will be described in more detail.

[0086] First particle

[0087] The first particle PTC1 may include an olivine-structured lithium compound represented by Formula 1: Li a1 Fe x1 B1 y1 PO 4-c1 .

[0088] In Formula 1, 0.8 < a1 ≤ 1.2, 0.95 ≤ x1 ≤ 0.999, 0.001 ≤ y1 ≤ 0.05, x1 + y1 = 1, and 0 ≤ c1 ≤ 0.05 may be satisfied, and B1 may be at least one element selected from the group consisting of Ti and transition metals having an oxidation number of 4. B1 may be a dopant doped in the first particle PTC1. Transition metals having an oxidation number of 4 include vanadium (V), chromium (Cr), zirconium (Zr), hafnium (Hf), molybdenum (Mo), niobium (Nb), and tantalum (Ta).

[0089] The benefits provided by the first particle PTC1 include cost efficiency, structural stability, and excellent life characteristics. The first particle PTC1 contains Fe as a main component, so it is relatively inexpensive, and due to its structural stability, it has relatively small chemical changes even after repeated charge / discharge.

[0090] Reference Figure 7 and Figure 9 The first PTC1 particle can be in the form of a single particle. In this document, a single particle can refer to a single type of particle without grain boundaries within it. A single particle can refer to a single particle morphologically present in an independent phase (where particles do not aggregate), a particle with an integral structure, a particle with a monolithic structure, or a non-aggregated particle. For example, a single particle can be a single crystal. Alternatively, a single particle can be a particle containing several crystals. A single particle can be in an isolated form. Alternatively, a single particle can be in the form of about 2 to about 100 single particles attached to each other.

[0091] The first particle PTC1 may include at least one first primary particle. In one embodiment, the first particle PTC1 may be spherical or elliptical in shape, with the first primary particle attached therein. In another embodiment, even when the first primary particle is attached, the first particle PTC1 may not have a spherical shape, but rather an irregular shape. Throughout the specification, the term "attached" is used to describe a single particle, while "agglomerate" is used to describe a secondary particle, to distinguish between the two. For reference, even a single particle may consist of primary particles attached in a manner that forms a cloud-like structure.

[0092] The first PTC1 particle can be provided in various sizes. For example, the first PTC1 particle can have an average diameter of about 0.5 μm to about 2.5 μm or about 1 μm. The minimum diameter of the first PTC1 particle (e.g., the particle size of the smaller first PTC1 particle, i.e., as used herein, "first primary particle" refers to the first PTC1 particle whose size corresponds to the minimum particle size) can be about 100 nm to about 500 nm or about 200 nm to about 300 nm.

[0093] In this implementation, the average diameter can be measured using a particle size analyzer. Average diameter (D) 50 It can indicate the diameter of particles with a cumulative volume of approximately 50 vol% in the particle size distribution.

[0094] In an implementation, the average diameter (size) of the first primary particle can be indicated by measuring the diameter of approximately 30 first primary particles randomly selected from an electron microscope image of the first particle PTC1.

[0095] Dopant can control the uniform growth of the first primary particles of PTC1. Therefore, dopant can improve the charge / discharge efficiency, low-temperature characteristics, and lifespan characteristics of rechargeable lithium batteries.

[0096] In one embodiment, the first PTC1 particle may include a coating on its surface. The coating may cover the entire surface of the first PTC1 particle or a portion of its surface. The first particle includes a coating containing carbon. The coating may include elemental carbon and / or carbon-containing compounds. The coating may provide the first PTC1 particle with improved structural stability and improved electrical conductivity.

[0097] The coating may further comprise at least one metal-containing compound selected from titanium-containing compounds and compounds containing transition metals with an oxidation state of 4. The metal-containing compound (such as titanium-containing compounds and compounds containing transition metals with an oxidation state of 4) may be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a complex thereof, or a mixture thereof. The metal-containing compound may further comprise other metallic or non-metallic elements. For example, the metal-containing compound may further comprise lithium.

[0098] In an embodiment, the first PTC1 particles may further include a grain boundary coating on the surface of each first primary particle. The grain boundary coating may be present within the first PTC1 particles. The grain boundary coating may be formed along the interfaces between the first primary particles within the first PTC1 particles. That is, the grain boundary coating may indicate a layer formed by material coated on the grain boundaries within the first PTC1 particles. The grain boundary coating may include elemental carbon and / or carbon-containing compounds. The grain boundary coating may further include at least one metal-containing compound selected from titanium-containing compounds and compounds containing a transition metal with an oxide number of 4.

[0099] The interior of the first PTC1 can refer to the entire interior of the first PTC1 excluding its surface. For example, the interior of the first PTC1 can refer to a region with a depth of about 10 nm from the surface of the first PTC1, or a region with a depth of about 10 nm to about 2 μm.

[0100] The first PTC1 particle may further include a coating, thereby providing enhanced structural stability and a uniform coating formed on the surface of the first PTC1 particle. Additionally, the first PTC1 particle may further include a coating, thereby providing improved electrical conductivity.

[0101] The first PTC1 particle may further include carbon (carbon element) derived from the above-described coating. The first PTC1 particle may have a carbon element content of about 0.5 wt% to about 5 wt%, about 0.5 wt% to about 3 wt%, or about 1.0 wt% to about 2 wt%. The first PTC1 particle may have a lower carbon element content than the third PTC3 particle (described below).

[0102] Second particle

[0103] The second particle PTC2 may include the following from formula 2: Li a2Ni x2 Co y2 B2 z2 O 2-c2 The layered lithium compound represented by

[0104] In Formula 2, 0.8 < a2 ≤ 1.2, 0.9 ≤ x2 ≤ 1.05, 0.03 ≤ y2 ≤ 0.10, 0.01 ≤ z2 ≤ 0.05, and 0 ≤ c2 ≤ 0.05 can be satisfied, and B2 can be at least one element selected from the group consisting of Al and Mn. B2 can be Al.

[0105] In one or more embodiments, in Chemical Formula 2, 0.9 ≤ x2 ≤ 0.94, 0.05 ≤ y2 ≤ 0.09, 0.01 ≤ z2 ≤ 0.05, x2 + y2 + z2 = 1, and 0 ≤ c2 ≤ 0.05 can be satisfied. The second particle PTC2 provides benefits such as high capacity and high energy density.

[0106] The second particle PTC2 is a nickel-based active material and may include a lithium nickel composite oxide. For example, the second particle PTC2 may include a high-nickel cathode active material containing a high content of nickel. The high-nickel cathode active material can achieve high capacity and high performance.

[0107] In an embodiment, the second particle PTC2 may include a second coating on its surface. The second coating can effectively prevent the structural collapse caused by repeated charge / discharge. Accordingly, the life characteristics of the rechargeable lithium battery can be improved.

[0108] The second coating may include an aluminum-containing compound, a titanium-containing compound, a magnesium-containing compound, a zirconium-containing compound, a molybdenum-containing compound, a niobium-containing compound, or a combination thereof. The metal-containing compound in the second coating can be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a complex thereof, or a mixture thereof. The metal-containing compound may further include other metal or non-metal elements. For example, the second coating may further include lithium, manganese, and / or nickel.

[0109] The method for measuring the amount of metal in the second coating of the second particle PTC2 may include performing scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM-EDS) on the second particle PTC2. Through this analysis, the contents of aluminum, titanium, magnesium, zirconium, molybdenum, and / or niobium in the second coating can be determined. In addition to SEM-EDS, the methods for measuring the metal content in the second coating may include inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma optical emission spectroscopy (ICP-OES), etc.

[0110] The second PTC2 particle may have a smaller Brunor-Emmett-Taylor (BET) specific surface area than the first PTC1 particle. The second PTC2 particle may have a BET specific surface area of ​​approximately 0.3 to approximately 0.6. The BET specific surface area indicates the surface area per unit mass. The smaller the BET, the smaller the contact surface between the positive electrode active material and the positive electrode current collector, resulting in lower resistance and greater adhesion relative to the electrode plate. That is, positive electrode active material containing second PTC2 particles with a small BET specific surface area is advantageous for preparing electrode plates with a small amount of binder.

[0111] The second PTC2 particle can be in the form of a single particle and / or a secondary particle. For example, the second PTC2 particle can be in the form of only a single particle, only a secondary particle, or a mixture of single and secondary particles. In embodiments, when having a bimodal form in which single and secondary particles are mixed, the second PTC2 particle can have an improved density. Reference will be made below. Figure 7 , Figure 10 and Figure 11 The second particle PTC2 is described as a single particle and the second particle PTC2 is described as a secondary particle.

[0112] In the implementation method, refer to Figure 10 The second PTC2 particle can be in the form of a single particle. In this document, a single particle can refer to a single type of particle without grain boundaries within it. A single particle can refer to a single particle morphologically present in an independent phase (where particles do not aggregate), a particle with an integral structure, a particle with a monolithic structure, or a non-aggregated particle. A single particle can be, for example, a single crystal. Alternatively, a single particle can be a particle containing several crystals. A single particle can be in an isolated form. Alternatively, a single particle can be in the form of about 2 to about 100 single particles attached to each other.

[0113] When the second PTC2 particle is a single particle, it may include at least one second primary particle. In one embodiment, the second PTC2 particle may be spherical or elliptical in shape with the second primary particle attached thereto. In another embodiment, even when the second primary particle is attached, the second PTC2 particle may not have a spherical shape, but rather an irregular shape. Compared to when the second PTC2 particle is in the form of a secondary particle, the structure of the second PTC2 particle can be less defined when it is a single particle with the second primary particle attached thereto. This means that the second PTC2 particle can have a more irregular shape.

[0114] When the second particle is a single particle, the second particle PTC2 can have an average diameter of approximately 3 μm to approximately 10 μm. The average diameter of the second particle PTC2 can be larger than the average diameter of the first particle PTC1. In an embodiment, the average diameter can be measured using a particle size analyzer. Average diameter (D) 50 This indicates the diameter of particles whose cumulative volume is approximately 50 vol% in the particle size distribution. The average diameter of the second particle (D) 50 It can be larger than the average diameter (D) of each of the first and third particles mentioned above (described below). 50 ).

[0115] refer to Figure 9 and Figure 10 When the second particle PTC2 is a single particle, the average size of the second primary particle of the second particle PTC2 can be greater than the average size of the first primary particle of the first particle PTC1.

[0116] In another embodiment, reference Figure 11 The second PTC2 particle can be in the form of a secondary particle. The secondary particle can be polycrystalline, indicating that at least two secondary primary particles are aggregated therein. That is, a single second PTC2 particle can comprise multiple aggregated secondary primary particles NNP2 (…). Figure 7 The second PTC2 particle can be spherical or elliptical in shape.

[0117] When the second particle is a secondary particle, the second PTC2 particle can have an average diameter of approximately 10 μm to approximately 14 μm. (Reference) Figure 9 and Figure 11 The average diameter of the second particle PTC2 can be equal to or greater than the average diameter of the first particle PTC1. In an embodiment, the average diameter can be measured using a particle size analyzer. Average diameter (D...) 50 It can indicate the diameter of particles with a cumulative volume of approximately 50 vol% in the particle size distribution.

[0118] In another embodiment, reference Figure 7 The second particle can exist in a bimodal form, where a single PTC2 (SP) particle and a secondary PTC2 (PC) particle are mixed. When it exists in a bimodal form, the second particle can have a further improved density. Figure 7As shown, the second particle PTC2 (PC) as a secondary particle can be in a form in which at least two second primary particles NNP2 are coalesced. The second particle PTC2 (SP) as a single particle can be in a form including at least one second primary particle. The second particle PTC2 (SP) as a single particle has a second primary particle with a size larger than that of the second particle PTC2 (PC) as a secondary particle. Even when the second primary particles are attached, the second particle PTC2 (SP) may not have a spherical shape but an irregular shape.

[0119] Third particle

[0120] The third particle PTC3 can include an olivine-structured lithium compound represented by Formula 3: Li a3 Fe x3 B3 y3 PO 4-c3 as shown.

[0121] In Formula 3, 0.8 < a3 ≤ 1.2, 0.95 ≤ x3 ≤ 0.999, 0.001 ≤ y3 ≤ 0.05, x3 + y3 = 1, and 0 ≤ c3 ≤ 0.05 are satisfied, and B3 is at least one of Ti and a transition metal with an oxidation number of 4. B3 can be a dopant doped in the third particle PTC3.

[0122] The third particle PTC3 provides benefits including low cost, high structural stability, and excellent life characteristics. In particular, when the third particle PTC3 contains Fe as a component, it is relatively inexpensive, and due to its structural stability, its chemical change is relatively small even after repeated charge / discharge.

[0123] The third particle PTC3 can be in the form of secondary particles. Referring to Figure 8 and Figure 12 , the secondary particles can be in a polycrystalline form, which is a form in which at least two third primary particles NNP3 are coalesced. That is, one third particle PTC3 can include a plurality of third primary particles NNP3 coalesced together. The third particle PTC3 can be in a spherical or elliptical shape.

[0124] Compared with a lithium compound with an olivine structure in the form of a single particle, a lithium compound with an olivine structure in the form of secondary particles can have a greater effect in reducing the battery resistance.

[0125] The dopant can have the effect of controlling the uniform growth of the third primary particles NNP3 of the third particle PTC3. The dopant provides a rechargeable lithium battery with improved charge / discharge efficiency, low-temperature characteristics, and life characteristics.

[0126] In this embodiment, the third PTC3 particle may include a coating on its surface. The coating may completely cover the surface of the third PTC3 particle or may partially cover the surface of the third PTC3 particle. For example, the coating may include elemental carbon and / or carbon-containing compounds. Through the coating, the third PTC3 particle can provide improved structural stability and electrical conductivity.

[0127] The coating may further comprise at least one metal-containing compound selected from titanium-containing compounds and compounds containing transition metals with an oxidation state of 4. The metal-containing compound (such as titanium-containing compounds and compounds containing transition metals with an oxidation state of 4) may be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a complex thereof, or a mixture thereof. The metal-containing compound may further comprise other metallic or non-metallic elements. The metal-containing compound may further comprise lithium.

[0128] The third PTC3 particle may further include a grain boundary coating on the surface of each third primary particle NNP3. The grain boundary coating may be present within the third PTC3 particle. The grain boundary coating may be formed along the interfaces between the third primary particles NNP3 within the third PTC3 particle. That is, the grain boundary coating may indicate a layer formed by material coated on the grain boundaries within the third PTC3 particle. The grain boundary coating may include elemental carbon and / or carbon-containing compounds. The grain boundary coating may further include at least one metal-containing compound selected from titanium-containing compounds and compounds containing a transition metal with an oxide number of 4.

[0129] The interior of the third PTC3 particle can refer to the entire interior of the third PTC3 particle excluding its surface. For example, the interior of the third PTC3 particle can refer to a region with a depth of about 10 nm from the surface of the third PTC3 particle, or a region with a depth of about 10 nm to about 2 μm.

[0130] The third PTC3 particle further includes a grain boundary coating, thereby providing enhanced structural stability and a uniform coating formed on the surface of the third PTC3 particle. Additionally, the third PTC3 particle further includes a grain boundary coating, thereby providing improved electrical conductivity.

[0131] The third PTC3 particle may further include carbon derived from the coating and / or grain boundary coating. The third PTC3 particle may have a carbon content of about 0.5 wt% to about 10 wt%, about 1 wt% to about 3 wt%, or about 1.0 wt% to about 2.0 wt%. When the third PTC3 particle is in the form of a secondary particle, the third PTC3 particle may have a higher carbon content than the first PTC1 particle.

[0132] The third PTC3 particle may have an average diameter of about 2 μm to about 15 μm, about 3 μm to about 10 μm, or about 3 μm to about 7 μm. For example, the third PTC3 particle may have an average diameter of about 5 μm. In an embodiment, the average diameter may be measured using a particle size analyzer. Average diameter (D) 50 It can indicate the diameter of particles with a cumulative volume of approximately 50 vol% in the particle size distribution.

[0133] The third primary particle NNP3 may have an average size (diameter) of about 200 nm or less. For example, the third primary particle NNP3 may have an average size of about 10 nm to about 200 nm, about 20 nm to about 200 nm, about 50 nm to about 200 nm, or about 100 nm to about 200 nm. In an embodiment, the average size of the third primary particle NNP3 may indicate the diameter measured by randomly selecting about 30 third primary particles NNP3 on an electron micrograph of the positive electrode active material. The size of the third primary particle NNP3 may be uniform.

[0134] The size (diameter) of the third primary particle NNP3 of the third PTC3 can be smaller than the size of the first primary particle of the first PTC1. For example, the size of the third primary particle NNP3 of the third PTC3 can be about 100 nm smaller than the size of the first primary particle of the first PTC.

[0135] When the average diameter of the third PTC3 particle and the average diameter of the third primary NNP3 particle meet the above range and the size of the third primary NNP3 particle is uniform, the rechargeable lithium battery containing the third PTC3 particle and the third primary NNP3 particle can have improved charge / discharge capacity and low-temperature capacity.

[0136] The third PTC3 particle can have a porosity of approximately 20% to approximately 40%. The span values ​​of the third PTC3 particle analyzed using a particle size analyzer can be approximately 0.3 to approximately 0.75. Porosity (n) can be defined as the pore volume (V). p Divide by the total volume of the particles (V) t ), or n = V p / V t The span value is determined by (D) 90 -D 10 ) / D 50 Indicated. As used in this article, the term "D" 10 "D" refers to the average diameter of particles when the cumulative percentage reaches 10% by volume in the particle size distribution, and is used as a term "D" in this document. 90 "This refers to the average diameter of the particles when the cumulative percentage reaches 90% of the particle size distribution."

[0137] First positive electrode active material layer

[0138] Figure 7 An enlarged view showing the first positive electrode active material layer ATL1 of the positive electrode for a rechargeable lithium battery according to an embodiment of the present disclosure.

[0139] refer to Figure 7 The first positive electrode active material layer ATL1 may include a first particle PTC1, a second particle PTC2, and a first functional additive FAD1. The first functional additive FAD1 may include a first binder BND1 and a first conductive material CDM1. Although not shown in the figures, the second particle PTC2 may be in the form of secondary particles or may be in a bimodal form as a mixture of single particles and secondary particles.

[0140] The first positive electrode active material layer ATL1 comprises a mixture of first particles PTC1 and second particles PTC2, thereby overcoming the limitations of lithium iron phosphate-based positive electrode active materials, such as low capacity and low energy density. That is, together, the benefits of lower production cost of the first particles PTC1 and higher capacity and energy density of the second particles PTC2 can be achieved.

[0141] The first positive electrode active material layer ATL1 comprises a mixture of first particles PTC1 and second particles PTC2 having a small BET. Accordingly, the weight ratio of the first functional additive FAD1 in the first positive electrode active material layer ATL1 can be reduced. The weight ratio of the first functional additive FAD1 in the first positive electrode active material layer ATL1 can be defined as the weight of the first functional additive FAD1 relative to the total weight of the first positive electrode active material layer. If the particle size is too small, the adhesion between the positive electrode current collector and the positive electrode active material can be reduced, which can increase resistance. As a result, the electrode plate can become difficult to process and a larger amount of binder may be required. According to embodiments of the present disclosure, the first positive electrode active material layer ATL1 includes second particles PTC2, which have a smaller BET than lithium iron phosphate positive electrode active materials. This makes the first positive electrode active material layer ATL1 advantageous for electrode plate fabrication. The weight ratio of the first functional additive FAD1 in the first positive electrode active material layer ATL1 can be, for example, from about 2.4 wt% to about 4.0 wt%.

[0142] The weight ratio of the first functional additive FAD1 in the first positive electrode active material layer ATL1 may be lower than or equal to the weight ratio of the second functional additive FAD2 in the second positive electrode active material layer ATL2 (as described below). The ratio of the weight ratio of the second functional additive FAD2 (i.e., the weight ratio of the second functional additive FAD2 in the second positive electrode active material layer ATL2) to the weight ratio of the first functional additive FAD1 (i.e., the weight ratio of the first functional additive FAD1 in the first positive electrode active material layer ATL1) may be about 1.0 to about 2.03.

[0143] The amount of the first binder BND1 relative to 100 parts by weight of the first positive electrode active material layer ATL1 can be about 1.2 parts by weight to about 2.0 parts by weight. The amount of the first conductive material CDM1 relative to 100 parts by weight of the first positive electrode active material layer ATL1 can be about 1.2 parts by weight to about 2.0 parts by weight. The amount of the first binder BND1 in the first positive electrode active material layer ATL1 can be lower than the amount of the second binder BND2 in the second positive electrode active material layer ATL2 (described below). When the first positive electrode active material layer ATL1 meets the content range of the first binder and the first conductive material, the battery capacity and energy density can be maximized, and the electrode plates can be easily processed.

[0144] The first binder BND1 is used to adhere the positive electrode active material particles PTC1 and PTC2, and also to adhere the positive electrode active material particles PTC1 and PTC2 to the positive electrode current collector COL1. Examples of the first binder BND1 are polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, and nylon. However, embodiments of this disclosure are not limited to these examples.

[0145] The first conductive material CDM1 can be used to impart conductivity to the electrodes. Any material that does not cause chemical changes and is conductive can be used in the battery. Examples of the first conductive material CDM1 include: carbon-based materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes); metallic materials, including copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers (such as polyphenylene derivatives); or mixtures thereof.

[0146] The first positive electrode active material layer ATL1 can be in contact with the surface of the positive electrode current collector COL1. Figure 6 ).

[0147] The first positive electrode active material layer ATL1 may have a thickness T1. In an embodiment, T1 may increase with the increase of the weight of the first particle PTC1 and / or the second particle PTC2 included in the first positive electrode active material layer ATL1.

[0148] The first positive electrode active material layer contains less carbon than the second positive electrode active material layer. The amount of carbon included in the first positive electrode active material layer can be defined as the weight of the carbon element included in the first positive electrode active material layer relative to the weight of the first positive electrode active material layer. That is, it can be defined as the weight of carbon included in the first positive electrode active material layer / the weight of the first positive electrode active material layer. The amount of carbon can be measured, for example, using carbon-sulfur analysis. However, the method for measuring the carbon content (amount) is not limited to this.

[0149] Second positive electrode active material layer

[0150] Figure 8 An enlarged view showing the second positive electrode active material layer ATL2 of the positive electrode for a rechargeable lithium battery according to an embodiment of the present disclosure.

[0151] refer to Figure 8 The second positive electrode active material layer ATL2 may include a third particle PTC3 and a second functional additive FAD2. The second functional additive FAD2 may include a second binder BND2 and a second conductive material CDM2.

[0152] The second binder BND2 is used to adhere the positive electrode active material particles PTC3. Examples of the second binder BND2 are polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, and nylon. However, embodiments of this disclosure are not limited to these examples. The second binder BND2 may be the same as or different from the first binder BND1 described above.

[0153] The second conductive material CDM2 can be used to impart conductivity to the electrodes. Any material that does not cause chemical changes and is electrically conductive can be used in the battery. Examples of the second conductive material CDM2 may include: carbon-based materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes); metallic materials, including copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers (such as polyphenylene derivatives); or mixtures thereof. The second conductive material CDM2 may be the same as or different from the first conductive material CDM1 described above.

[0154] The amount of the second binder BND2 relative to 100 parts by weight of the second positive electrode active material layer ATL2 can be about 2.0 parts by weight to about 2.5 parts by weight. The amount of the second conductive material CDM2 relative to 100 parts by weight of the second positive electrode active material layer ATL2 can be about 2.0 parts by weight to about 2.5 parts by weight. The amount of the second binder BND2 in the second positive electrode active material layer ATL2 can be greater than the amount of the first binder BND1 in the first positive electrode active material layer ATL1. Optionally, the amount of the second binder BND2 in the second positive electrode active material layer ATL2 relative to the amount of the first binder BND1 in the first positive electrode active material layer ATL1 can be about 1.0 to about 2.03. When the second positive electrode active material layer ATL2 meets the range relative to the amounts of the second conductive material and the second binder, the battery capacity can be maximized, and the electrode plate can be easily processed.

[0155] The weight ratio of the second functional additive FAD2 in the second positive electrode active material layer ATL2 can be greater than the weight ratio of the first functional additive FAD1 in the first positive electrode active material layer ATL1. The weight ratio of the second functional additive FAD2 in the second positive electrode active material layer ATL2 can be about 4.0 wt% to about 5.0 wt%.

[0156] The weight ratio of the second functional additive FAD2 to the first functional additive FAD1 (weight ratio of the second functional additive FAD2 / weight ratio of the first functional additive FAD1) can be approximately 1.0 to approximately 2.03. When the weight ratio of the second functional additive FAD2 to the first functional additive FAD1 meets this range, the positive electrode active material layer AML1 exhibits improved adhesion to the positive electrode current collector COL1. Consequently, the battery capacity and energy density can be maximized, and the electrode plates can be easily processed.

[0157] The second positive electrode active material layer ATL2 can be coated on the surface of the first positive electrode active material layer ATL1. The surface of the first positive electrode active material layer ATL1 can be a surface that does not contact the positive electrode current collector COL1. For example, the positive electrode current collector COL1, the first positive electrode active material layer ATL1, and the second positive electrode active material layer ATL2 can be arranged sequentially, such as... Figure 6 As explained in the text.

[0158] The second positive electrode active material layer ATL2 may have a thickness T2. In an embodiment, T2 may increase with the increase of the weight of the third particle PTC3 included in the second positive electrode active material layer ATL2.

[0159] A positive electrode including a first positive electrode active material layer and a second positive electrode active material layer

[0160] Figure 6 A cross-sectional view of the positive electrode for a rechargeable lithium battery according to an embodiment of the present disclosure is shown. (Reference) Figure 6 As described above, the positive electrode 10 may include a positive electrode current collector COL1 and a positive electrode active material layer AML1. The positive electrode active material layer AML1 may be provided on the positive electrode current collector COL1.

[0161] The positive electrode active material layer AML1 may include positive electrode active material particles PTC1, PTC2, and PTC3 (i.e., first particle PTC1, second particle PTC2, and third particle PTC3). Relative to 100 wt% of the positive electrode active material layer AML1, the positive electrode active material layer AML1 may contain approximately 90 wt% to approximately 99 wt% of the positive electrode active material particles PTC1, PTC2, and PTC3.

[0162] The positive electrode active material layer AML1 may include binders BND1 and BND2 and conductive materials CDM1 and CDM2. Relative to 100 wt% of the positive electrode active material layer AML1, the positive electrode active material layer AML1 may contain approximately 0.5 wt% to approximately 5 wt% of each of binders BND1 and BND2 and conductive materials CDM1 and CDM2.

[0163] The positive electrode active material layer AML1 may include a first positive electrode active material layer ATL1 and a second positive electrode active material layer ATL2. Because the first positive electrode active material layer ATL1 is located below the second positive electrode active material layer ATL2, the positive electrode active material layer AML1 can contain a large amount of nano-sized olivine-based lithium compounds, while simultaneously increasing adhesion to the positive electrode current collector. As a result, the electrode plate can be easily fabricated, and the resistance in the electrode plate can be reduced. Ultimately, this leads to a rechargeable lithium battery with superior performance.

[0164] The first positive electrode active material layer ATL1 may have a thickness T1. In an embodiment, T1 may increase with the increase of the weight of the first particle PTC1 and / or the second particle PTC2 included in the first positive electrode active material layer ATL1. The second positive electrode active material layer ATL2 may have a thickness T2. In an embodiment, T2 may increase with the increase of the weight of the third particle PTC3 included in the second positive electrode active material layer ATL2.

[0165] The thickness ratio T1:T2 of the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2 can be approximately 3:7 to approximately 7:3. For example, the thickness ratio T1:T2 of the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2 can be approximately 5:5. When the thickness ratio T1:T2 of the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2 is within these ranges, the positive electrode active material layer AML1 has improved adhesion relative to the positive electrode current collector COL1. Accordingly, the battery capacity and energy density can be maximized, and the electrode plates can be easily processed.

[0166] In embodiments of this disclosure, such as Figure 6 and Figure 7 As shown, a first positive electrode active material layer ATL1 is located between the positive electrode current collector COL1 and the second positive electrode active material layer ATL2. The first positive electrode active material layer ATL1 contains a suitable ratio of second particle PTC2 and first particle PTC1. This configuration improves the adhesion of the electrode plate and reduces the need for binder BND1. Furthermore, it leads to improvements in capacity, density characteristics, high-temperature stability, and lifetime characteristics. Moreover, the inclusion of second particle PTC2 in a bimodal form (including a mixture of single particles and secondary particles) further enhances the density.

[0167] The amount of the first PTC1 particle is approximately 20 wt% to approximately 40 wt% relative to the total amount of the first PTC1 particle, the second PTC2 particle, and the third PTC3 particle included in the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2. For example, the amount of the first PTC1 particle is approximately 35 wt% relative to the total amount of the first PTC1 particle, the second PTC2 particle, and the third PTC3 particle included in the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2.

[0168] The amount of the second particle PTC2 is approximately 10 wt% to approximately 30 wt% relative to the total amount of the first particle PTC1, the second particle PTC2, and the third particle PTC3 included in the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2. For example, the amount of the second particle PTC2 is approximately 20 wt% to approximately 30 wt% relative to the total amount of the first particle PTC1, the second particle PTC2, and the third particle PTC3 included in the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2.

[0169] The amount of the third PTC3 particle is approximately 30 wt% to approximately 40 wt% relative to the total amount of the first PTC1, second PTC2, and third PTC3 particles included in the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2. For example, the amount of the third PTC3 particle is approximately 35 wt% relative to the total amount of the first PTC1, second PTC2, and third PTC3 particles included in the first positive electrode active material layer ATL1 and the second positive electrode active material layer ATL2.

[0170] The amount of the second PTC2 particles is about 30 wt% to about 60 wt% relative to the total amount of the first PTC1 particles and the second PTC2 particles included in the first positive electrode active material layer ATL1. For example, the amount of the second PTC2 particles is about 45 wt% to about 50 wt% relative to the total amount of the first PTC1 particles and the second PTC2 particles included in the first positive electrode active material layer ATL1.

[0171] When the amounts of the first PTC1, the second PTC2, and the third PTC3 particles meet the above-mentioned range, the positive electrode active material layer AML1 can have improved adhesion relative to the positive electrode current collector COL1. Accordingly, a rechargeable lithium battery with reduced resistance can be provided. Furthermore, when the amounts of the first PTC1, the second PTC2, and the third PTC3 particles meet the above-mentioned range, a rechargeable lithium battery with superior performance can be provided.

[0172] Preparation examples, embodiments, and comparative examples of this disclosure have been described. However, the following embodiments are presented only as implementations of this disclosure, and this disclosure is not limited to the following embodiments.

[0173] Preparation Example 1: Preparation of the first particle (single particle form)

[0174] Ferric phosphate precursor (FePO4), lithium carbonate, and titanium dioxide were mixed in a molar ratio of Fe:Li:Ti = 1:1.03:0.004. 10 wt% glucose was further added to the mixture. The mixture was then wet-milled by ball milling. The mixture was evaporated to dryness on a heated tray, and then placed in a vacuum oven at 85°C and dried for 4 hours. The dried mixture was calcined at 750°C for 10 hours under a nitrogen atmosphere. The calcined product was milled at 8000 rpm to obtain first particles in the form of single particles. The first particles had an average diameter of 0.5 μm to 2.5 μm. The first primary particles of the first particles had a size of 200 nm to 300 nm.

[0175] Preparation Example 2: Preparation of the second particle (single particle form)

[0176] Ni 0.92 Co0.07 Al 0.01 (OH)₂ and LiOH were mixed in a molar ratio of (Ni+Co+Al):Li = 1:1.05, and the mixture was subjected to a first heat treatment at 810°C for 8 hours in an oxygen atmosphere to obtain Li 1.05 Ni 0.92 Co 0.07 Al 0.01 The composition of O2 and its average diameter (D) 50 The oxide is approximately 4 μm in size. Alumina was added to the oxide, and the mixture was then subjected to a second heat treatment at 740 °C for 8 hours in an oxygen atmosphere to prepare second particles in single-particle form. The second particles are composed of the formula LiNi. 0.92 Co 0.07 Al 0.01 O2 represents.

[0177] Preparation Example 3: Preparation of Third Particles (Secondary Particle Form)

[0178] Ferric phosphate precursor (FePO4), lithium carbonate, and titanium dioxide were mixed in a molar ratio of Fe:Li:Ti = 1:1.03:0.004. 10 wt% glucose was further added to the mixture to obtain a slurry mixture. The slurry mixture was spray-dried at a spray pressure of 0.5 MPa and a temperature of 230 °C, and then evaporated to dryness. The dried mixture was calcined at 750 °C for 10 hours in a nitrogen atmosphere to obtain third particles in the form of secondary particles. The third particles had an average diameter (D) of approximately 3 μm to approximately 7 μm. 50 The third primary particle of the third particle has a size (diameter) of 100 nm to 200 nm.

[0179] Example 1: Preparation of a positive electrode including a first positive electrode active material layer and a second positive electrode active material layer

[0180] The first particle from Preparation Example 1 and the second particle from Preparation Example 2 were dispersed in N-methylpyrrolidone with a conductive material (carbon black) and a binder (polyvinylidene fluoride) to prepare a first positive electrode active material slurry. The third particle from Preparation Example 3 was dispersed in N-methylpyrrolidone with a conductive material (carbon black) and a binder (polyvinylidene fluoride) to prepare a second positive electrode active material slurry.

[0181] A first positive electrode active material slurry is coated onto the positive electrode current collector and dried to form a first positive electrode active material layer. A second positive electrode active material slurry is coated onto the first positive electrode active material layer and dried to form a second positive electrode active material layer.

[0182] This forms a double-layer positive electrode active material layer, with the first, second, and third particles in the double-layer positive electrode active material layer existing in a weight ratio of 35:30:35. A positive electrode in which the positive electrode current collector, the first positive electrode active material layer, and the second positive electrode active material layer are stacked in this order is prepared using a roller press.

[0183] Example 2

[0184] The positive electrode was prepared in essentially the same manner as in Example 1, except that a second particle in a bimodal form was used instead of the single-particle form of the second particle from Preparation Example 2.

[0185] The method for preparing the second particle in a bimodal form is as follows:

[0186] Ni 0.92 Co 0.07 Al 0.01 (OH)₂ and LiOH were mixed in a molar ratio of (Ni+Co+Al):Li = 1:1.05, and a flux was added to the mixture. The mixture was then subjected to a first heat treatment at 750°C for 15 hours in an oxygen atmosphere to obtain particles after the first heat treatment.

[0187] The particles after the first heat treatment were ground using a jet mill at a pressure of 3 bar, and then washed with distilled water. After washing, alumina was added to the particles after the first heat treatment, and the mixture was dried at 150°C for 12 hours. The dried mixture was then subjected to a second heat treatment at 700°C for 15 hours in an oxygen atmosphere to prepare second particles in the form of secondary particles.

[0188] The second particles in the form of secondary particles and the second particles in the form of single particles from Preparation Example 2 were mixed at a weight ratio of 2:8 to prepare the second particles in the form of bimodal particles.

[0189] Comparative Example 1: Preparation of a positive electrode including a positive electrode active material layer

[0190] The first particles from Preparation Example 1 and the second particles from Preparation Example 2 were mixed at a weight ratio of 30:70 and dispersed together with a conductive material (carbon black) and a binder (polyvinylidene fluoride) in N-methylpyrrolidone to prepare a positive electrode active material slurry. The positive electrode active material slurry was coated onto a positive electrode current collector and dried to prepare a monolayer positive electrode.

[0191] Comparative Example 2

[0192] The positive electrode was prepared in essentially the same manner as in Comparative Example 1, except that the first particle of Preparation Example 1 and the second particle of Preparation Example 2 were mixed in a weight ratio of 40:60.

[0193] Comparative Example 3

[0194] The positive electrode was prepared in essentially the same manner as in Comparative Example 1, except that the first particle of Preparation Example 1 and the second particle of Preparation Example 2 were mixed in a weight ratio of 50:50.

[0195] Comparative Example 4

[0196] The positive electrode was prepared in essentially the same manner as in Comparative Example 1, except that the first particle of Preparation Example 1 and the second particle of Preparation Example 2 were mixed in a weight ratio of 60:40.

[0197] Comparative Example 5

[0198] The positive electrode was prepared in essentially the same manner as in Comparative Example 1, except that the first particle of Preparation Example 1 and the second particle of Preparation Example 2 were mixed in a weight ratio of 70:30.

[0199] Comparative Example 6

[0200] The positive electrode was prepared in essentially the same manner as in Comparative Example 1, except that the first particle of Preparation Example 1 and the second particle of Preparation Example 2 were mixed in a weight ratio of 80:20.

[0201] Comparative Example 7

[0202] The positive electrode was prepared in essentially the same manner as in Comparative Example 1, except that the first particle of Preparation Example 1 and the second particle of Preparation Example 2 were mixed in a weight ratio of 90:10.

[0203] Comparative Example 8

[0204] The first particle from Preparation Example 1, the second particle from Preparation Example 2, and the third particle from Preparation Example 3 were mixed in a weight ratio of 35:30:35 and dispersed together with a conductive material (carbon black) and a binder (polyvinylidene fluoride) in N-methylpyrrolidone to prepare a positive electrode active material slurry. The positive electrode active material slurry was coated onto a positive electrode current collector and dried to prepare a monolayer positive electrode.

[0205] Comparative Example 9

[0206] The positive electrode was prepared in essentially the same manner as in Example 1, except that the weights of the first binder, the first conductive material, the second binder, and the second conductive material were changed. The weight changes were adjusted so that the weight ratio of the second functional additive to the first functional additive was 0.8.

[0207] Comparative Example 10

[0208] The positive electrode was prepared in essentially the same manner as in Example 1, except that the weights of the first binder, the first conductive material, the second binder, and the second conductive material were changed. The weight changes were adjusted so that the weight ratio of the second functional additive to the first functional additive was 2.5.

[0209] Comparative Example 11

[0210] A positive electrode containing a lithium compound with an olivine structure in the form of single particles was prepared. A positive electrode active material slurry was prepared using the first particle from Preparation Example 1, and then the positive electrode active material slurry was coated onto a positive electrode current collector and dried to prepare a monolayer positive electrode.

[0211] Comparative Example 12

[0212] A positive electrode containing a lithium compound with an olivine structure in the form of secondary particles was prepared. A positive electrode active material slurry was prepared using the third particle from Preparation Example 3, and then the positive electrode active material slurry was coated onto a positive electrode current collector and dried to prepare a monolayer positive electrode.

[0213] Preparation of rechargeable lithium batteries

[0214] A 2032-type coin half-cell was prepared using a prepared positive electrode and a lithium metal counter electrode. A separator with a thickness of approximately 16 μm, formed of a porous polyethylene (PE) membrane, was placed between the positive electrode and the lithium metal counter electrode, and an electrolyte was injected to prepare a rechargeable lithium battery. The electrolyte was prepared by mixing 1.3 M LiPF6 with a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:4:3.

[0215] Evaluation Example 1: Analysis of the surface of the active material in the positive electrode

[0216] exist Figure 9 , Figure 10 and Figure 12 The image shows SEM images of each of the first, second, and third particles prepared in Preparation Examples 1 to 3.

[0217] refer to Figure 9 As can be seen, the first particle of Preparation Example 1 according to this disclosure is in the form of a single particle.

[0218] refer to Figure 10 As can be seen, the second particle prepared according to Example 2 of this disclosure is in the form of a single micron-sized particle. (Reference) Figure 9 and Figure 10It can be seen that when the second particle is in the form of a single particle, the average diameter of the second particle (D) 50 ) is greater than the average diameter of the first particle (D) 50 ).

[0219] refer to Figure 11 As can be seen, the second particle according to the embodiments of this disclosure is in the form of a spherical secondary particle in which fine second primary particles of nanoscale size are aggregated.

[0220] refer to Figure 12 As can be seen, the third particle according to Preparation Example 3 of this disclosure is in the form of a spherical secondary particle in which fine third primary particles of nanoscale aggregate are aggregated.

[0221] Evaluation Example 2: Evaluation of Positive Electrode Active Material

[0222] The powder compaction density (PD) of the positive electrode active materials of the Examples and Comparative Examples was measured, and the results are shown in Table 1 below. The powder compaction density was measured by placing 3 grams of the positive electrode active material into a powder compaction mold and applying a force of approximately 4.0 US tons for approximately 30 seconds. The powder compaction density (PD) of the positive electrode active materials according to the embodiments was 2.65 g / cc to 2.73 g / cc. The weight ratios of the first, second, and third particles in Table 1 refer to the percentage of the weight of the first, second, and third particles relative to the total weight of the first, second, and third particles, respectively.

[0223] Table 1

[0224]

[0225] Notice, *1 Use the second particle, which has a bimodal shape.

[0226] Evaluation Example 3: Evaluation of Battery Characteristics

[0227] The characteristics of rechargeable lithium batteries prepared using positive electrode active materials from the respective examples and comparative examples were evaluated.

[0228] For the initial charge / discharge, the rechargeable lithium battery was initially charged at 25°C with a constant current and constant voltage (approximately 4.2V, approximately 0.05C cutoff) at 0.2C. After resting for 10 minutes, it was discharged to 3.0V with a constant current of 0.2C. The initial charge capacity at 0.2C and the initial discharge capacity at 0.2C were obtained, and the efficiency (efficiency at 0.2C (%)) was expressed as the initial charge capacity at 0.2C / the initial discharge capacity at 0.2C. The average voltage was then evaluated. Subsequently, the charge / discharge cycle was repeated 50 times at 45°C and 1.0C (approximately 4.2V, approximately 0.05C cutoff) / 1.0C (approximately 3.0V, approximately 0.05C cutoff) to measure the initial discharge capacity at 0.2C after the 50th cycle, and the lifetime (lifetime at 1C (%, 50 cycles)) was expressed as the initial discharge capacity at 0.2C after the 50th cycle / the initial discharge capacity at 0.2C. A rechargeable lithium battery was prepared and initially charged at approximately 25°C under constant current and constant voltage (approximately 4.2V, cutoff at approximately 0.05C) at 0.2C. After resting for 10 minutes, it was discharged to 3.0V at a constant current of 0.2C. It was then recharged at -20°C under constant current (approximately 0.2C) and constant voltage (approximately 4.2V, cutoff at approximately 0.05C), and then discharged again at a constant current (approximately 0.2C) until the voltage reached 3.0V to measure the discharge capacity (discharge capacity at -20°C). The average voltage was obtained by integrating the area under the discharge voltage curve (voltage-capacity plot) after the initial charge and discharge of the battery cell, and then dividing the integral by the discharge capacity. The energy density was then calculated by charging and discharging the battery at a rate of 0.2C / 0.2C within a voltage range of 3.0V to 4.45V at 25°C. Energy density was obtained using the following equation: {Average drive voltage (V) × Capacity (Ah) / Cell weight (kg)}, where capacity was calculated by multiplying the positive electrode weight (g) by the discharge capacity (mAhg). The rechargeable lithium battery was charged to SOC50 at a constant current of 0.2C and discharged at 1.0C for 1 second to record voltage and current, then discharged at a constant current of 0.2C for 1 second to record another voltage and current, thereby calculating the DC internal resistance (DCIR). DCIR was measured as ΔV / ΔI (voltage change / current change). The resulting battery performance is shown in Tables 2 and 3 below.

[0229] The weight of the second particle in Table 2 indicates the weight of the second particle relative to the total weight of the first, second, and third particles.

[0230] Table 2

[0231]

[0232] Notice, *2 Use the second particle, which has a bimodal shape.

[0233] Table 3

[0234]

[0235] Referring to Table 2, it can be seen that the rechargeable lithium battery including the positive electrode according to Examples 1 and 2 has the same or higher levels of efficiency, capacity, lifetime, voltage, resistance, and energy density as the rechargeable lithium battery including the positive electrode according to Comparative Example 8. That is, even when the mixing ratio of the first particle, the second particle, and the third particle is the same, the battery including the bilayer positive electrode active material performs better than the battery including only the monolayer positive electrode active material.

[0236] Referring to Table 3, it can be seen that the rechargeable lithium battery including the positive electrode according to Comparative Example 12 has greater efficiency, low-temperature capacity, lifespan, and resistance than the rechargeable lithium battery including the positive electrode according to Comparative Example 11. In particular, the resistance is significantly reduced. That is, when the first particle is included in the form of a secondary particle rather than a single particle, the resistance of the olivine-structured lithium compound is significantly reduced. This disclosure includes a third particle to prepare an olivine-based positive electrode active material, wherein the third particle is in the form of a secondary particle, thus having a greater effect on reducing resistance.

[0237] Evaluation Example 4: Evaluation of Resistance and Adhesion

[0238] The DC internal resistance (DCIR) and adhesion of rechargeable lithium batteries prepared using positive electrode active materials from the respective examples and comparative examples were evaluated, and the results are shown in Table 4 below.

[0239] For initial charge / discharge, the rechargeable lithium battery was initially charged at approximately 25°C under constant current and constant voltage (approximately 4.2V, approximately 0.05C cutoff) conditions at 0.2C. After resting for 10 minutes, it was discharged to 3.0V at a constant current of 0.2C, and then the average voltage was evaluated. The rechargeable lithium battery was charged to SOC50 at a constant current of 0.2C and discharged at 1.0C for 1 second to record the voltage and current, and then discharged at a constant current of 0.2C for 1 second to record another voltage and current, thereby calculating the DC internal resistance (DCIR). DCIR was measured as ΔV / ΔI (voltage change / current change).

[0240] The amounts of the first functional additive and the second functional additive, as well as the weight ratio of the second functional additive to the weight ratio of the first functional additive (weight ratio of FAD2 / weight ratio of FAD1) were calculated.

[0241] Table 4

[0242]

[0243] Referring to Table 4, it can be seen that the rechargeable lithium battery including the positive electrode according to Examples 1 and 2 has a lower DC internal resistance (DCIR) than the rechargeable lithium battery including the positive electrode according to Comparative Examples 9 and 10. That is, when the weight ratio of the second functional additive to the weight ratio of the first functional additive (weight ratio of FAD2 / weight ratio of FAD1) meets the target range of this disclosure, the adhesion to the positive electrode current collector can be increased.

[0244] The positive electrode according to this disclosure comprises a first particle and a third particle, each having an olivine structure, thus enabling lower production costs and improved average voltage.

[0245] The positive electrode according to this disclosure includes a second particle having a layered structure, thus having improved capacity and energy density.

[0246] The positive electrode according to this disclosure has a second particle and a first particle mixed and disposed in a first positive electrode active material layer, thus making the electrode plate easier to prepare.

[0247] The positive electrode according to this disclosure has first, second, and third particles that are mixed in optimal proportions and placed to form a bilayer structure, thereby improving battery characteristics and facilitating the fabrication of electrode plates.

Claims

1. A positive electrode for a rechargeable lithium battery, the positive electrode comprising: A positive electrode current collector; A first positive electrode active material layer on the positive electrode current collector; And A second positive electrode active material layer on the first positive electrode active material layer, Wherein the first positive electrode active material layer comprises first particles of an olivine-structured compound represented by Formula 1, second particles of a layered compound represented by Formula 2, a first conductive material, and a first binder, Wherein the second positive electrode active material layer comprises third particles of an olivine-structured compound represented by Formula 3, a second conductive material, and a second binder, Wherein the first particles are in the form of single particles, Wherein the third particles are in the form of secondary particles, Wherein the first binder and the first conductive material constitute a first functional additive, Wherein the second binder and the second conductive material constitute a second functional additive, Wherein the weight ratio of the second functional additive in the second positive electrode active material layer to the weight ratio of the first functional additive in the first positive electrode active material layer is 1.0 to 2.03, Wherein Formula 1 is: Li a1 Fe x1 B1 y1 PER 4-c1 Where 0.8 < a1 ≤ 1.2, 0.95 ≤ x1 ≤ 0.999, 0.001 ≤ y1 ≤ 0.05, x1 + y1 = 1, and 0 ≤ c1 ≤ 0.05, and B1 is at least one of Ti and a transition metal with an oxidation number of 4, Wherein Formula 2 is: Li a2 Ni x2 Co y2 B2 z2 O 2-c2 Where 0.8 < a2 ≤ 1.2, 0.9 ≤ x2 ≤ 1.05, 0.03 ≤ y2 ≤ 0.10, 0.01 ≤ z2 ≤ 0.05, and 0 ≤ c2 ≤ 0.05, and B2 is at least one of Al and Mn, and Wherein Formula 3 is: Li a3 Fe x3 B3 y3 PO 4-c3 Where 0.8 < a3 ≤ 1.2, 0.95 ≤ x3 ≤ 0.999, 0.001 ≤ y3 ≤ 0.05, x3 + y3 = 1, and 0 ≤ c3 ≤ 0.05, and B3 is at least one of Ti and a transition metal with an oxidation number of 4.

2. The positive electrode for a rechargeable lithium battery according to claim 1, wherein B2 in Formula 2 is Al, the second particles are in the form of single particles, and the second particles have an average diameter of 3 μm to 10 μm.

3. The positive electrode for a rechargeable lithium battery as claimed in claim 1, wherein B2 in formula 2 is Al, the second particle is in the form of a secondary particle, wherein a plurality of second primary particles aggregate to form each of the secondary particles, and the second particle has an average diameter D of 10 μm to 14 μm. 50 .

4. The positive electrode for a rechargeable lithium battery as described in claim 1, wherein the first particle comprises a first primary particle having an average diameter D of 200 nm to 300 nm. 50 Furthermore, the first particle has an average diameter D of 0.5 μm to 2.5 μm. 50 .

5. The positive electrode for a rechargeable lithium battery as claimed in claim 1, wherein the third particle is in the form of a secondary particle in which a plurality of third primary particles are aggregated, the third primary particles having an average diameter D of 100 nm to 200 nm. 50 Furthermore, the third particle has an average diameter D of 3μm to 7μm. 50 .

6. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the second particles are in a bimodal form including single particle form and secondary particle form.

7. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the second particles have a BET specific surface area smaller than that of the first particles.

8. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the third particles have a porosity of 20% to 40%.

9. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the span value of the third particles is 0.3 to 0.

75.

10. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 3:7 to 7:

3.

11. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the amount of the second particles is 10 wt% to 30 wt% relative to the total weight of the first particles, the second particles, and the third particles included in the first positive electrode active material layer and the second positive electrode active material layer.

12. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the amount of the second particles is 20 wt% to 30 wt% relative to the total weight of the first particles, the second particles, and the third particles included in the first positive electrode active material layer and the second positive electrode active material layer.

13. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the amount of the first binder is 1.2 parts by weight to 2.0 parts by weight relative to 100 parts by weight of the first positive electrode active material layer, and wherein the amount of the second binder is 2.0 parts by weight to 2.5 parts by weight relative to 100 parts by weight of the second positive electrode active material layer.

14. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the ratio of the amount of the second binder in the second positive electrode active material layer to the amount of the first binder in the first positive electrode active material layer is 1.0 to 2.

03.

15. The positive electrode for a rechargeable lithium battery according to claim 1, wherein the first particles and the third particles include a coating containing carbon element, and wherein the first particles contain less carbon element than the third particles.

16. A positive electrode for a rechargeable lithium battery, the positive electrode comprising: a positive electrode current collector; a first positive electrode active material layer on the positive electrode current collector; and a second positive electrode active material layer on the first positive electrode active material layer, wherein the first positive electrode active material layer includes first particles of an olivine-structured compound represented by Formula 1, second particles of a layered compound represented by Formula 2, a first conductive material, and a first binder, wherein the second positive electrode active material layer includes third particles of an olivine-structured compound represented by Formula 3, a second conductive material, and a second binder, wherein the first particles are in the form of single particles, wherein the third particles are in the form of secondary particles, wherein the amount of the first binder in the first positive electrode active material layer is less than the amount of the second binder in the second positive electrode active material layer, wherein Formula 1 is: Li a1 Fe x1 B1 y1 PER 4-c1 where 0.8 < a1 ≤ 1.2, 0.95 ≤ x1 ≤ 0.999, 0.001 ≤ y1 ≤ 0.05, x1 + y1 = 1, and 0 ≤ c1 ≤ 0.05, and B1 is at least one of Ti and a transition metal with an oxidation number of 4, wherein Formula 2 is: Li a2 Ni x2 Co y2 B2 z2 O 2-c2 where 0.8 < a2 ≤ 1.2, 0.9 ≤ x2 ≤ 1.05, 0.03 ≤ y2 ≤ 0.10, 0.01 ≤ z2 ≤ 0.05, and 0 ≤ c2 ≤ 0.05, and B2 is at least one of Al and Mn, and wherein Formula 3 is: Li a3 Fe x3 B3 y3 PO 4-c3 where 0.8 < a3 ≤ 1.2, 0.95 ≤ x3 ≤ 0.999, 0.001 ≤ y3 ≤ 0.05, x3 + y3 = 1, and 0 ≤ c3 ≤ 0.05, and B3 is at least one of Ti and a transition metal with an oxidation number of 4.

17. The positive electrode for a rechargeable lithium battery according to claim 16, wherein the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 3:7 to 7:

3.

18. The positive electrode for a rechargeable lithium battery according to claim 16, wherein the amount of the second particles is 10 wt% to 30 wt% relative to the total weight of the first particles, the second particles, and the third particles included in the first positive electrode active material layer and the second positive electrode active material layer.

19. The positive electrode for a rechargeable lithium battery according to claim 16, wherein the amount of the first binder is 1.2 parts by weight to 2.0 parts by weight relative to 100 parts by weight of the first positive electrode active material layer, and where the amount of the second binder is 2.0 parts by weight to 2.5 parts by weight relative to 100 parts by weight of the second positive electrode active material layer.

20. A rechargeable lithium battery comprising the positive electrode according to any one of claims 1 to 19.

Citation Information

Patent Citations

  • Apparatus and method for synchronizing true reality and virtual reality using artificial intelligence predictive models

    KR1020240057143A